A randomized trial of surgery alone versus surgery plus compression in the treatment of venous leg ulcers in patients with primary venous insufficiency - Milić, Dragan; Živić, Saša; Golubović, Mladjan; Bogdanović, Dragan; Lazarević, Milan; Lazarević, Konstansa (Vojnosanitetski pregled, 2021)
Background/Aim.Venous leg ulcers (VLU) are a significant health problem worldwide. It is well known that VLU are difficult to treat and that they have high tendency for recurrence. Compression therapy is the preferred treatment modality but there is growing evidence that correction of underlying venous disorder in early stages of the disease in addition to compression treatment may improve ulcer healing and reduce recurrence rate. Methods. An open, prospective, randomized, single-center study, with a 6-months follow-up was performed to determine the efficacy of two different treatment modalities (surgery alone versus surgery plus compression) in the treatment of VLU in patients with primary venous insufficiency. Patients with secondary venous insufficiency and/or thrombosis were excluded from the study. Overall, 71 patients were randomized (37 men, 34 women; mean age 60 years) into two groups: the group A – 34 patients who underwent surgical intervention (stripping) and postoperatively were treated with simple wound dressing only, and the group B – 37 patients who underwent surgical intervention (stripping) and wore a heelless open-toed elastic class III compression device knitted in tubular form –Tubulcus® (Laboratoires Innothera, Arcueil, France). All patients in group B were instructed to wear compression device continuously during the day and night. The study was performed at the Clinic for Cardiovascular and Transplant Surgery, Clinical Centre Niš (Serbia) with primary endpoint of the study being complete ulcer healing at 180 days. Results. The healing rate was 29.41% (10/34) in the group A, and 56.76% (21/37) in the group B (p < 0.01). Mean healing time in the group A was 141 ± 15 days, and in the group B it was 98 ± 12 days (Log-rank life table analysis: p < 0.001). Conclusion. This study suggests that for VLU in patients with primary venous insufficiency, surgery plus compression therapy provides higher healing rate and faster healing time compared to surgery only.